2014
DOI: 10.1259/bjr.20140296
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of diagnostic value of 18F-FDG PET or PET/CT for detecting lymph node and distant metastases in patients with nasopharyngeal carcinoma

Abstract: The authors Guohua Shen and Wenjie Zhang contributed equally to this work.Objective: We performed this meta-analysis to comprehensively assess the diagnostic performance of positron emission tomography (PET) or PET/CT for detecting lymph node and distant metastases in patients with nasopharyngeal carcinoma (NPC). Methods: Through a search of four English and three Chinese databases (January 1990 to June 2013), pooled estimated sensitivity, specificity and diagnostic odds ratio (DOR) were calculated based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…[30][31][32] A recent meta-analysis survey has suggested that PET-CT is a highly reliable diagnostic tool for detecting LN metastasis. [33] Prognostic efficacy of SUV, MTV, TLG parameters of LNs before treatment has been studied by many investigators, but there have been conflicting conclusions. [9,10,17,18] Chang et al have reported that neither SUVmax nor TLG of metastatic LNs is a reliable predictor of OS in NPC patients, while Lin et al demonstrated that patients with a high SUVmax, TLG, and MTV of LNs have a worse OS prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] A recent meta-analysis survey has suggested that PET-CT is a highly reliable diagnostic tool for detecting LN metastasis. [33] Prognostic efficacy of SUV, MTV, TLG parameters of LNs before treatment has been studied by many investigators, but there have been conflicting conclusions. [9,10,17,18] Chang et al have reported that neither SUVmax nor TLG of metastatic LNs is a reliable predictor of OS in NPC patients, while Lin et al demonstrated that patients with a high SUVmax, TLG, and MTV of LNs have a worse OS prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Now, MRI can not only well demonstrate T-primary tumor, but also identify cervical lymph nodes. So far, the diagnosis of lymph node metastases for radiologist and radiation oncologists is based mainly on size criteria when interpreting cervical adenopathy on MR images of patients with NPC, [ 16 17 18 ] such as malignancy was usually suggested when the shortest axial diameter of cervical nodes in level I–VII was at least 10 mm, a cluster of more than 3 borderline size nodes was another imaging reference for metastasis, central necrosis reliably identified in tumor foci larger than 3 mm was considered as 100% specificity of diagnosis on node metastasis, and extracapsular spread was usually indicators of metastasis in large nodes, etc. However, nonenlarged nodes may harbor malignancy, whereas reactive nodes may be enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity analyses of English publications and studies having five items of low risk/concern also showed relatively poor values in LR- of 0.200 and 0.201, respectively. Moreover, compared with the results from two previous meta-analyses, our study showed greater between-study consistency and obviously lower pooled sensitivity 21, 31. Because of the limited number of topic-related studies, we only summarized the diagnostic pergormance of other modalities on a per‑patient basis in Table 4.…”
Section: Resultsmentioning
confidence: 79%